Foveocrotaphus gen. n. and F. burmanicus sp. n.: a new genus and species of Physocrotaphini from Myanmar (Coleoptera: Carabidae: Anthiinae) - Anichtchenko, Alexander (Zootaxa, 2014)
Foveocrotaphus gen. nov. and new species F. burmanicus from Myanmar is described. The new genus is similar to Physocrotaphus Parry, with respect to shape and structure of ligula and paraglossae. The two genera can be diagnosed easily by median tooth of mentum, bifid in Physocrotaphus, i.e. Foveocrotaphus gen. n. has simple, narrow and pointed. Is distinguishable from all other known Physocrotaphini genera by narrower pronotum, very stout ligula combined with long and simple median tooth of mentum and by male sternites 2 and 3 with one big shared median depression.